2019
DOI: 10.1007/s00213-019-05311-2
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating the optimal dose of flupentixol decanoate in the maintenance treatment of schizophrenia—a systematic review of the literature

Abstract: RationaleThe licensed dose range for the long-acting injectable antipsychotic flupentixol decanoate (Depixol®) in the treatment of schizophrenia is very broad. This provides little useful direction to prescribers and may ultimately result in patients receiving unnecessarily high doses.ObjectivesWe aimed to estimate the effect of dose of flupentixol decanoate on relapse rates in schizophrenia and on tolerability by expanding on an earlier review and including non-RCT and German-language studies, as well as usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The initial and maintenance dose of flupentixol decanoate for most patients is 20–40 mg every 2–3 weeks [ 45 ]. Although the recommended dose range of flupentixol decanoate is broad, recent evidence suggests that doses close to or below the minimum recommended dose (as low as 10 mg every 2 weeks) are effective [ 47 ]. Flupentixol is predominantly metabolized by sulfoxidation and lacks interactions associated with CYP inducers or inhibitors [ 45 ].…”
Section: First-generation Long-acting Injectable (Lai) Antipsychoticsmentioning
confidence: 99%
“…The initial and maintenance dose of flupentixol decanoate for most patients is 20–40 mg every 2–3 weeks [ 45 ]. Although the recommended dose range of flupentixol decanoate is broad, recent evidence suggests that doses close to or below the minimum recommended dose (as low as 10 mg every 2 weeks) are effective [ 47 ]. Flupentixol is predominantly metabolized by sulfoxidation and lacks interactions associated with CYP inducers or inhibitors [ 45 ].…”
Section: First-generation Long-acting Injectable (Lai) Antipsychoticsmentioning
confidence: 99%
“…It has been suggested that these wide dosage ranges are not supported by the available evidence and may lead to some patients receiving unnecessarily high doses. For example, it has been proposed that the optimal dose of LAI flupentixol is probably between 20 mg and 40 mg every 2 weeks 19 ; we found that one in five prescriptions for this LAI antipsychotic medication were for doses above this upper threshold, thus potentially leading to an increased side-effect burden for little additional therapeutic benefit. The evidence suggests that most of the common side effects of antipsychotic medication, including EPS, are dose-related.…”
Section: Discussionmentioning
confidence: 74%
“…The prescribed dose of LAI flupentixol was greater than the suggested optimal dose of 20–40 mg every 2 weeks in 224 (19%) cases. 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is noted that previous dose-response Calculations were derived using references listed in Table 1 (Kegeles et al, 2008;Nyberg et al, 1995;Reimold et al, 2007). studies for flupentixol decanoate suggest that doses above 40 mg/ fortnight may not result in any additional benefit seen (Bailey and Taylor, 2019).…”
Section: Resultsmentioning
confidence: 99%